2016
DOI: 10.3892/or.2016.5273
|View full text |Cite
|
Sign up to set email alerts
|

Loss of miR-638 promotes invasion and epithelial-mesenchymal transition by targeting SOX2 in hepatocellular carcinoma

Abstract: Aberrant expression of microRNAs has been identified as regulators of biological processes of hepatocellular carcinoma (HCC) by negatively regulating protein-coding mRNAs. Several studies have demonstrated that miR-638 expression was dysregulated in various human cancers. However, the clinical significance and underlying mechanisms of miR-638 involved in HCC remain to be elucidated. Herein, we confirmed that a reduced miR-638 expression was present in HCC tissues and cell lines. Our clinical analysis revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…This result was in consistence with others. For instance, attenuated miR-638-SOX2 axis was reported to promote the invasion by inducing epithelialmesenchymal transition in non-small-cell lung cancer [21], colorectal carcinoma [36], hepatocellular carcinoma [22]. Remarkably, Vanner and Boumahdi et al revealed SOX2 was important in regulating cancer stem-like cells [30,37].…”
Section: Figure 5: Knockdown Of Sox2 Antagonized the Pro-invasion Andmentioning
confidence: 99%
“…This result was in consistence with others. For instance, attenuated miR-638-SOX2 axis was reported to promote the invasion by inducing epithelialmesenchymal transition in non-small-cell lung cancer [21], colorectal carcinoma [36], hepatocellular carcinoma [22]. Remarkably, Vanner and Boumahdi et al revealed SOX2 was important in regulating cancer stem-like cells [30,37].…”
Section: Figure 5: Knockdown Of Sox2 Antagonized the Pro-invasion Andmentioning
confidence: 99%
“…miR-638 is upregulated and acts as a tumor promoting miRNA in prostate cancer (7), esophageal carcinoma (9), breast cancer (9) and melanoma (10). Nevertheless, miR-638 was demonstrated to be downregulated and to function as a tumor suppressive miRNA in gastric (8,11), cervical (12) and breast cancer (13), and hepatocellular carcinoma (14). The methylation status, expression level and biological roles of miR-638 have not been investigated in Ec.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, several studies have reported that miR-638 suppressed cell invasion, proliferation and epithelial-mesenchymal transition by downregulating SOX2 gene expression in non-small cell lung cancer (NSCLC) and colorectal carcinoma cells (27,28). As for HCC, there are limited studies that have investigated miR-638 and SOX2 expression and the clinical significance of this (29,30). Notably, whether or not an association exists between these two molecules remains to be elucidated.…”
Section: Expression Of Microrna 638 and Sex-determining Region Y-box mentioning
confidence: 99%